Effect of Applying an Organic Amendment on the Persistence of Tebuconazole and Fluopyram in Vineyard Soils - Eliseo Herrero-Hernández; María Soledad Andrades; María J. Sánchez-Martín; Jesús M. Marín-Benito; María Sonia Rodríguez-Cruz (Agronomy, 2023)
The persistence of fluopyram and tebuconazole has been studied in different crops and agricultural soils. However, the behaviour of these fungicides may be altered when they are applied as a combined formulation in organically amended vineyard soils under field conditions. The purpose of this study is to evaluate the effect of applying spent mushroom substrate (SMS) or this residue re-composted with ophite (SMS + OF) on the adsorption, dissipation, and mobility of the fungicides fluopyram and tebuconazole in vineyard soils. Triplicate 10 m2 plots per treatment were set up in two different vineyard soils in the eastern La Rioja region: silt loam (ARN1) and sandy loam (ARN2), respectively, with low organic carbon (OC) content. The organic residues SMS and SMS + OF were applied at doses of 25 and 100 Mg ha−1. The adsorption distribution coefficients (Kd) increased when SMS and SMS + OF were applied, especially at the higher dose (100 Mg ha−1). The dissipation curve of both compounds fitted a two-phase kinetic model, with a very fast initial dissipation rate, followed by slower prolonged dissipation during the second phase. The dissipation half-lives (DT50) ranged between 4.7 and 26.3 days for fluopyram and between 2.3 and 6.3 days for tebuconazole in the different soils, increasing for fluopyram in the ARN1 amended with SMS and SMS + OF. The fungicide residues at 15–30 cm depth were lower in the unamended and amended sandy loam soil (ARN2), indicating that fungicides are dissipated mainly in the topsoil. The results indicate different dissipation mechanisms for both fungicides, as the adsorption by soil OC prevented the dissipation of fluopyram but facilitated the dissipation of tebuconazole, probably due to the formation of non-extractable residues.